Efficient high-level parallel programming - Botorog, George Horaţiu; Kuchen, Herbert (Theoretical computer science, 1998)
Algorithmic skeletons are polymorphic higher-order functions that represent common parallelization patterns and that are implemented in parallel. They can be used as the building blocks of parallel and distributed applications by embedding them into a sequential language. In this paper, we present a new approach to programming with skeletons. We integrate the skeletons into an imperative host language enhanced with higher-order functions and currying, as well as with a polymorphic type system. We thus obtain a high-level programming language, which can be implemented very efficiently. We then present a compile-time technique for the implementation of the functional features which has an important positive impact on the efficiency of the language. After describing a series of skeletons which work with distributed arrays, we give two examples of parallel algorithms implemented in our language, namely matrix multiplication and Gaussian elimination. Run-time measurements for these and other applications show that we approach the efficiency of message-passing C up to a factor between 1 and 1.5.